Pharmacokinetics of linezolid in critically ill patients. (2nd June 2016) - Sazdanovic, Predrag; Jankovic, Slobodan M.; Kostic, Marina; Dimitrijevic, Aleksandra; Stefanovic, Srdjan
ABSTRACT: Introduction : Linezolid is an oxazolidinone antibiotic active against Gram-positive bacteria, and is most commonly used to treat life-threatening infections in critically ill patients. The pharmacokinetics of linezolid are profoundly altered in critically ill patients, partly due to decreased function of vital organs, and partly because life-sustaining drugs and devices may change the extent of its excretion. Areas covered : This article is summarizes key changes in the pharmacokinetics of linezolid in critically ill patients. The changes summarized are clinically relevant and may serve as rationale for dosing recommendations in this particular population. Expert opinion : While absorption and penetration of linezolid to tissues are not significantly changed in critically ill patients, protein binding of linezolid is decreased, volume of distribution increased, and metabolism may be inhibited leading to non-linear kinetics of elimination; these changes are responsible for high inter-individual variability of linezolid plasma concentrations, which requires therapeutic plasma monitoring and choice of continuous venous infusion as the administration method. Acute renal or liver failure decrease clearance of linezolid, but renal replacement therapy is capable of restoring clearance back to normal, obviating the need for dosage adjustment. More population pharmacokinetic studies are necessary which will identify and quantify the influence of various factors on clearance and plasma concentrations of linezolid in critically ill patients.